Development and validation of a specific sandwich ELISA for determination of soybean allergens and its application in processed foods. (June 2022) - Zhu, Liyan; Li, Siyue; Sun, Lirui; Zhao, Jinlong; Huang, Jianlian; Jiang, Yinmei; Wan, Shuo; Pavase, Tushar Ramesh; Li, Zhenxing
Abstract: Soybean allergens are commonly quantified using enzyme-linked immunosorbent assays (ELISAs) with antibodies produced by the single allergen. To enhance the specificity and avoid the false-negative results, the sandwich ELISA method was developed using a rabbit anti-bulk soybean proteins polyclonal antibody and a goat anti- bulk soybean proteins polyclonal antibody as the detection and capture antibody, respectively. The proposed method has been optimized and validated according to the requirements of the AOAC Allergen Community. The method has a wide quantification range from 0.0625 μg/mL to 6.0 μg/mL and can quantify soybean residues at a low level down to 0.25 mg/kg with satisfactory accuracy (recovery range from 89.5% to 118%) and precision (RSDs < 16.67%). The new approach performs high specificity to soybean residues without obvious cross-reactivity to common allergic foods and legumes, and has been successfully applied to detect soybean proteins in commercial foods. Our data demonstrated that the established sandwich ELISA method has a higher specificity, accuracy, and robustness that could meet the quantification requirements for soybean allergens. Graphical Abstract: ga1 Highlights: The sELISA with high specificity for multi soybean allergens detection has been developed. This proposed method completely meets the requirements of the AOAC Allergen Community. The approach could successfully monitor soybean residues in commercial food products. The optimization of capture and detection antibody is essential for ELISA.